The Effect of Passive Ultrasonic Irrigation in Comparison with other Techniques on Removing Calcium Hydroxide from Root Canals: A Systematic Review - Samira Jamali; Fatima Betul Basturk; Maneesha Das; Rayane de Oliveira Pinto (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2019)
Background and aim: Residues may remain in canal extensions and irregularities after removing the medication from root canals with a file. These residues can only be removed with irrigation. The present systematic review and meta-analysis investigate the effect of various irrigation methods on the elimination of calcium hydroxide from root canals. Material and methods: A preliminary analysis included 225 articles. Two reviewers investigated all the available abstracts and titles and determined whether they were associated with the cleaning effectiveness of a variety of irrigation systems in removing calcium hydroxide. The conducted search involved the years between 2013-18. Results: The studies investigated lacked any standardization concerning the irrigation method used or the measurement of outcomes; for instance, the volume or the concentration of the irrigation solution. Conclusion: Although none of the methods examined could completely eliminate the calcium hydroxide dressing, activation methods resulted in better calcium hydroxide dressing removal compared to using master apical file or syringe irrigation only.